Design and Construction of Hydraulic Press. - Natukunda, Andrew (Kabale University, 2025)
The main aim of this project was to design and construct a hydraulic press from locally available materials which function by means of an incompressible fluid thereby transforming theoretical knowledge to practical one. This project is the best on Pascal’s Principle which states that ``pressure exerted anywhere in a confined incompressible fluid is transmitted equally in all directions throughout the liquid ’’. As a teacher in the making, I used nails, wood, syringes, tubes, cotton, empty battles, and a wand afterward to design a simple hydraulic press from locally available materials to transform theoretical work into practical skills for active teaching and learning.